PENYULUHAN DAN PELATIHAN MENJAGA KESEHATAN JIWA KELUARGA DI MASA PANDEMI COVID-19 - Yenny Yenny; Erita Istriana; Kartini Kartini; Irgy Prijenka Ardhanariswara; Caroline Anggraeni (JUARA: Jurnal Wahana Abdimas Sejahtera, 2021)
The high number of mental disorders in children and adolescents can not only affect learning achievement at school, but can also have a negative impact on their self-harming. The purpose of this counseling and training is to increase the knowledge of the activity participants on the factors that can trigger mental disorders in children and adolescents during the COVID-19 pandemic and improve skills in early detection of mental disorders in children and adolescents. Counseling and training held by online on Saturday, May 29, 2021. A total of 84 participants attended this activity consisting of principals, teachers, and parents of elementary and junior high school students of Tarsisius I, Jakarta. The results of the counseling and training showed an increase in the knowledge and skills of participants in the good pre-activity category from 50% to 86.9% after the activity. Increased knowledge and skills of identification and early detection of mental health disorders in children is needed for parents, caregivers, and teachers so that prevention and early intervention can be carried out before manifestations of mental health disorders arise in children. Efforts to maintain the mental health of children and adolescents require the participation of all parties around the child.